Immunogenicity of dupilumab in adult and pediatric patients with atopic dermatitis - Kamal, Mohamed A.; Kosloski, Matthew P.; Lai, Ching-Ha; Partridge, Michael A.; Rajadhyaksha, Manoj; Kanamaluru, Vanaja; Bansal, Ashish; Shabbir, Arsalan; Shumel, Brad; Ardeleanu, Marius; Richards, Susan M.; Yan, Hong; et al. (Frontiers in Immunology, 2024)
Background Development of anti-drug antibodies (ADAs) and neutralizing antibodies (NAbs) to monoclonal antibodies may adversely impact pharmacokinetics, efficacy, and/or safety. Objective To describe incidence, titer, and persistence of dupilumab ADAs and NAbs, and their effects on pharmacokinetics, efficacy, and safety in patients with atopic dermatitis (AD). Methods This analysis included seven phase 3 randomized, placebo-controlled (N=2,992) and two long-term open-label extension (N=2,287) trials of subcutaneous dupilumab in adults and pediatric patients with moderate-to-severe AD. ADA, NAb, and dupilumab concentration in serum were assessed using validated immunoassays. ADA impacts on efficacy (EASI) and safety were assessed. Results Treatment-emergent ADAs were observed in up to 8.6% (aged ≥18 years), 16.0% (12-17 years), 5.3% (6-11 years), and 2.0% (6 months to 5 years) dupilumab-treated patients. Among dupilumab-treated patients, ≤3.7% had persistent responses, <1% had high titers (≥10,000), and ≤5.1% were NAb-positive. NAbs were more common in patients with moderate- and high-titer ADA responses. High-titer ADAs, while infrequent, were the variable most associated with lower dupilumab concentrations in serum and loss of efficacy, independent of NAb status. Efficacy was generally similar in ADA-positive and -negative patients. For most patients with high- or moderate-titer ADAs, titers decreased and efficacy improved over time with continued dupilumab treatment. ADA-positive and -negative patients had similar incidences of treatment-emergent and serious treatment-emergent adverse events. One patient with high-titer ADAs developed serum sickness. Conclusion In patients with AD, ADAs and NAbs had minimal impact on dupilumab concentration, efficacy, and safety, except for high-titer ADAs in a small number of patients. Clinical trial registration ClinicalTrials.gov, identifiers (NCT02277743, NCT02277769, NCT02260986, NCT02395133, NCT01949311, NCT03054428, NCT03345914, NCT02612454, and NCT03346434).